A contextualização na matemática do ensino médio - Maioli, Marcia (2012)
This is a theoretical research that studies the contextualization established on national curricular documents as one of the pedagogic principles that structure the curricula on High School. The study stands for the contextualization as a potentially rich pedagogic principle to improve mathematic learning by the students, but it needs to be understood in its purposes and uses by different actors. For such, the investigation was developed based on bibliographic sources that involve studies about learning, comparison of meanings and language; curricular documents for High School; researches about contextualization on mathematical teaching and, aiming at investigating how are developed activities inspired on the contextualization of curricula that are practiced in class; it is also considered the set of dissertations involving Hypothetical Learning Paths developed on the research project in which this work is inserted. It could be verified that the contextualization implementation was not a simple action - nor even for professionals that are in touch with researches or theories that concern Mathematical Education. The National Curricular Parameters for High School outline that contextualizing the content that is aimed to be learned means, primarily, to assume that all knowledge involves a relation between subject and object. The idea of knowledge as a network of meanings defended by Machado and Pires; the process by which more relevant and inclusive concepts are presented is one in which the learner´s cognitive structure interacts with a new material presented to them as defended by Ausubel; the role of instruments and signs as mediators on the conversion of social relations according to higher mental functions considered by the studies of Vygotsky; the different language conceptions explored by Koch provide important clues about the relation processing between learning subject and study object. The contextualization is strongly related to the assignment of meanings to what is learned, and therefore, it embraces a cognitive aspect that cannot be neglected. Besides that, for the perspective established of learning, 10 knowledge is the product of activity context and culture in which it is developed and used, so the scholar culture influence cannot be ignored concerning what is learned in it